2019
DOI: 10.1016/j.tiv.2019.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory cytokines enhance dilatation of bile canaliculi caused by cholestatic antibiotics

Abstract: Many drugs can induce liver injury, characterized by hepatocellular, cholestatic or mixed hepatocellular-cholestatic lesions. While an inflammatory stress is known to aggravate hepatocellular injury caused by some drugs much less evidence exists for cholestatic features. In this study, the influence of pro-inflammatory cytokines (IL-6, IL-1β and TNF-α), either individually or combined, on cytotoxic and cholestatic properties of antibiotics was evaluated using differentiated HepaRG cells. Six antibiotics of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…At high concentrations (>6 mM), cholestatic injury was evidenced by dilation of BC, reduced bile acid efflux, and secretion of hepatocyte proinflammatory cytokines such as IL-6 and IL-1β. 1,2,12 The alteration of BC morphology by flucloxacillin was further confirmed by the current study when a lower concentration of drug was used (1.5 mM). Flucloxacillin treatment of primary human hepatocytes was also associated with the release of high-mobility group box 1 protein and dendritic cells exposed to flucloxacillin-treated hepatocyte supernatant secreted TNFα, IL-6, and IL-1β.…”
supporting
confidence: 72%
“…At high concentrations (>6 mM), cholestatic injury was evidenced by dilation of BC, reduced bile acid efflux, and secretion of hepatocyte proinflammatory cytokines such as IL-6 and IL-1β. 1,2,12 The alteration of BC morphology by flucloxacillin was further confirmed by the current study when a lower concentration of drug was used (1.5 mM). Flucloxacillin treatment of primary human hepatocytes was also associated with the release of high-mobility group box 1 protein and dendritic cells exposed to flucloxacillin-treated hepatocyte supernatant secreted TNFα, IL-6, and IL-1β.…”
supporting
confidence: 72%
“…The current findings also revealed that catalpol greatly reduced the contents of pro-inflammatory factors in the serum derived from model mice in a concentration-dependent manner. A recent study indicated that IL-6 and IL-1β may enhance the bile canaliculi dilatation caused by cholestatic antibiotics (36). It has also been found that ginsenoside can attenuate oxidative stress and the inflammatory response in rats with intrahepatic cholestasis (37).…”
Section: Discussionmentioning
confidence: 99%
“…Pro-inflammatory cytokines, such as TNF-α, IL-1β, and IL-6 and IL-8, produced by the inflammatory cells, such as KCs and bile duct cells stimulated by LPS, can contribute to the development of cholestasis by inducing a sustained decrease in the levels of bile acid transport proteins. [97][98][99] In the early stages of inflammation, TNF-α and IL-1β are involved in the downregulation of NTCP, while in the later stages of inflammation, they are regulated by IL-6. 100,101 Higher levels of IL-8 may be associated with the development of PBC and reflect the progression of the disease towards cirrhosis.…”
Section: Cytokinesmentioning
confidence: 99%